The main character in Carlos Fuentes’s Aura and a brief approach to the Iraqi novel - Fadil Hassan, Layla (2020)
At the end of the fifties, a series of Latin American writers appeared. In this group, known as Latin American Boom, was Carlos Fuentes. Fuentes shows us an initiation into the mysteries of time and personality. These myster- ies are implicit in his novel Aura (1962), which we will analyze in this brief investigation. There are themes of the Boom Literature in this novel, and traces of the difficult and distinguished history of Latin America. The imaginary world among Iraqi and Spanish writers is similar. The magical reality does not exist only in Latin America, but also in the countries of the Middle East, and many Arab writers took that subject into their literary works.